Sains Islam; Pemikiran Agus Purwanto dalam Buku Ayat-Ayat Semesta dan Nalar Ayat-Ayat Semesta - Yusuf, Mohamad Yasin (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2017)
ABSTRACT: This study is a study of thought associated with Agus PurwantoÃ¢â¬Å¸s thought in the book by the tittle Ayat- Ayat Semesta and Nalar Ayat-Ayat Semesta. According to Agus Purwanto thought in his book, he divides the relationship between Islam and science within 3 (three) kinds of models, namely: the Islamization of Science, Islamic of Scientification and Islamic Science. Islamization of Science is the model that made the discovery that the majority of modern science in the West, can be in accordance with the teachings of Islam. Islamic of Scientification is trying to find the basics of science to the teachings of Islam. While the Islamic Science seeks to make the Quran and as-Sunna as a base construction science. Of the three kinds of models, Agus Purwanto choose three clusters, namely the Islamic Science. Islamic Science is a science-based construction revelation. In this case, Agus Purwanto offer kauniyah 800 verses in the Quran to do the analysis of the text, which is then followed by observation and experimentation natural phenomena directly by using the scientific method.